Screening for Depressive Symptoms: Validation of the Center for Epidemiologic Studies Depression Scale (CES-D) in a Multiethnic Group of Patients With Diabetes in Singapore - Stahl, Dorit; Sum, Chee Fang; Lum, Shin Si; Liow, Pei Hsiang; Chan, Yiong Huak; Verma, Swapna; Chua, Hong Choon; Chong, Siow Ann (Diabetes care, 2008)
OBJECTIVE:--We determined the reliability and validity of the Center for Epidemiologic Studies Depression Scale (CES-D) against the DSM-IV-based diagnostic inventory, Schedule for Clinical Assessment in Neuropsychiatry (SCAN), in a multiethnic sample of adult subjects with diabetes attending a diabetes center in Singapore. RESEARCH DESIGN AND METHODS--A total of 522 subjects (74.7% Chinese, 11.1% Malay, and 14.2% Indian) completed culturally adapted versions of the CES-D; 291 subjects were administered the SCAN inventory. RESULTS:--The CES-D (cutoff score 16) showed high negative predictive values of more than 90% in all three ethnic groups. The prevalence of depressive symptoms (CES-D) and depression (SCAN) was significantly different between the Chinese and Indian subjects (CES-D 27.4 vs. 43.2%, P = 0.006); (SCAN 15.0 vs. 31.1%, P = 0.01). CONCLUSIONS:--The CES-D proved to be a reliable instrument for identifying patients with depressive symptoms in the multiethnic setting of this study.